ANALISIS KINERJA PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA PEMERINTAH KOTA DENPASAR TAHUN ANGGARAN 2014-2018 - Ni Made Susanti Dewantari; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2021)
This study aims to analyze the performance of the management of the regional income and expenditure budget (APBD) in Denpasar in terms of the government's financial ratios from 2014-2018. The data used in this study is the 2014-2018 Denpasar City budget data. The data collection technique is with documentation and interviews conducted in the city of Denpasar. The method used is comparative descriptive using several financial ratios. The results showed that based on the analysis of income variance, expenditure variance, and the ratio of independence in 2014-2015 said to be quite good, where the intent of the pattern of relationships between interference from the central government began to decrease. The ratio of effectiveness and efficiency ratio of PAD expenditure is said to be very effective and efficient in realizing regional taxes and levies. The ratio of routine expenditure to capital expenditure is said to be quite good. While the ratio of income and expenditure growth is said to be not good because there is a significant decrease and increase.